Estudio de mercado de las necesidades recreativas de los adolescentes de la ciudad de Quevedo, periodo 2010-2011 - Casares Litardo, Orlando Daniel (2011)
The investigation of market of the recreational necessities of the adolescents of the city of Quevedo, county of The Ríos, Ecuador, during the year 2010, he/she gave to know what time the adolescents dedicate to the recreation activities. The quantity and quality of the recreational centers and tourist places don't satisfy the necessities, this study is of utility for the sectional governments, secondary, visionary educational institutions of level that consider a priority the study of the recreational necessities, since will be an useful tool to the decentralized autonomous government of Quevedo and the educational institutions to the project in mention, it would be reached to develop an excellence youth coordinating the study with the activities recreacionales, not leaving space for the bad habits characteristic of the adolescence. The materials and methods that were used in the investigation of markets point out the size of the sample of the adolescents of the city of Quevedo, it was appealed the population of all the public and private schools of the city of Quevedo, the formula of the simple random sampling, the investigation was applied he/she consisted on carrying out surveys to the students of the high school, a bank of questions dedicated to the director or coordinator of the area of the autonomous decentralized government's of the city of Quevedo tourism with the purpose of determining the current situation of the places or places also settled down where it can be carried out acts or recreation events dedicated to the adolescents of the city of Quevedo. The methodology of this investigation consisted on one of exploratory type and of observation in the one that was revised physical and digital documents carefully to obtain information, tests or justifications has more than enough matters and investigations, on the other hand by means of the field investigation it was where they were applied technical and specific procedures linking students of high schools and government representatives besides visiting recreational places with the purpose of verifying the real situation of this places. Quevedo has three recreation places and three municipal tourist places, where they can carry out its recreational activities, located in the parishes Venus of the River Quevedo, The Guayacán, San Camilo and the Center of Quevedo. The recreational activities that they would like to carry out in the schools to the adolescents of the city of Quevedo are soccer 30,32%, swimming 7,82%, dances 12,87% and chess 9,84%. The time dedicated to the recreational activity in the educational establishments of the city 69,95% takes among one hour or more, while 19,95% takes inferior minutes at one hour. The main problem that disables him to participate in the recreational activities to the adolescents of the city of Quevedo with 24,47% is the factor time, economic factor with 21,28% and 15,43% that don't have recreational places in its sector. In view of the fact that the city of Quevedo has limited recreation places and tourist places consider the creation of new places of healthy esparcimiento in agreement with the private investment. To foment the linking among the sectional governments, to propose the development of the main activities that the adolescents would like to carry out like it is the soccer, swimming, it dances and chess. The demand of the recreational activities has a considerable margin of 65%, this great percentage level it should be considered on the part of the competent authorities for the development of the good one to live, integrating them in a productive way in our society, in the same way to find integration mechanisms to 35% that he/she doesn't carry out activity some and for ende to avoid that they group to undue societies. The reduced time that the adolescents have to visit some tourist place 62,67% gave him among one hour or more, while 22,61% takes inferior minutes of one hour and 14% he/she didn't answer for it which it should be programmed events and expeditions coordinated in the institutions where they are being educated. The diverse factors that disable to participate in the recreational activities or in some tourist place he/she gives the necessity to build thematic parks or of multiple uses in the diverse marginal urban and urban sectors of the canton Quevedo offering easiness to our adolescents of being integrated to recreational activities in their same town.